Integrated metabolism, network pharmacology, and pharmacokinetics to explore the exposure differences of the pharmacodynamic material basis in vivo caused by different extraction methods for Saussurea involucrata. (15th November 2022) - Yang, Lu; Lyu, Haiyan; Yiming, Ayixianmuguli; Xu, Xiangzhen; Ma, Chunling; Tu, Shun; Chen, Binbin; Liu, Mingyuan; Wu, Caisheng
Abstract: Ethnopharmacological relevance: Saussurea involucrata Kar.et Kir. ( S.I. ) has long been used as a precious national medicine and clinically proven to be an effective treatment for rheumatoid arthritis (RA) and cardiovascular diseases. In clinical practice, two extraction methods of S.I., including water decoction and alcohol extraction, are prescribed to treat the same conditions. Nevertheless, no study has been performed on the exposure differences of the pharmacodynamic material basis in vivo caused by different extraction methods. Aim of the study: Based on the integrated strategy of metabolism, network pharmacology, and pharmacokinetics, we aimed to reveal exposure differences in pharmacodynamic substances caused by different extraction methods. Materials and methods: Ultra-high-performance liquid chromatography-high-resolution mass spectrometry (UPLC-HRMS) was employed to identify the chemical constituents of S.I. extracts and the metabolites in vivo after administration. Based on the analysis of prototype components in vivo, the major exposure active constituents, potential therapeutic targets and possible pharmacological mechanisms in RA treatment were investigated using network pharmacological analysis. Seven critical active components, including quercetin, hispidulin, apigenin, chlorogenic acid, arctigenin, syringin, and umbelliferone, were quantitatively compared between the alcohol, and aqueous extraction methods, which had been confirmed by the reference substance. Results: The chemical comparison demonstrated that the types of chemicals in the two extracts were identical, mainly flavonoids, phenylpropanoids, coumarins, lignins, sesquiterpene lactones, and others, but the contents of the primary constituents in the aqueous extract were lower than those of the alcohol extract. A total of 30 prototype components and 174 metabolites were analyzed and identified in rat plasma, urine, fecal, and bile samples. Twenty-three prototype components were analyzed by network pharmacology, and seven critical active components were selected as representative markers for the pharmacokinetic study. Pharmacokinetic studies had shown that the Tmax values of apigenin, hispidulin, chlorogenic acid, arctigenin, and syringin after the oral administration of the alcohol extract were lower than those after the oral administration of the aqueous extract, and the above components in the alcohol extract could increase the absorption. Compared with the aqueous extract group, the Tmax and T1/2 of quercetin and umbelliferone were longer; it was suggested that alcohol extraction might have a slow-release and long-term effect on these two components. The relative bioavailability of apigenin, hispidulin, quercetin, chlorogenic acid, and umbelliferone in the alcohol extract group were higher than those in the aqueous extract group, which was consistent with the traditional clinical experience that alcohol extract could improve the efficacy of S.I. Conclusions: The major exposure active constituents in vivo were screened. The representative components that could be used in pharmacokinetics were determined by integrating network pharmacology and metabolism studies. The critical active compounds were quantitatively compared between the alcohol and aqueous extraction methods. This study clarified that flavonoids, coumarin, and phenylpropanoids might be the primary material basis that caused the exposure differences between aqueous and alcoholic extracts from S.I. . This research aimed to provide the basis of metabolism in vivo for further studying these pharmacodynamic differences. Graphical abstract: Image 1